Gerakan Islam Sempalan: Mitos Disintegrasi Dan Dialog Intraagama - Moch Muwaffiqillah (Universitas Islam Negeri Mataram, 2007)
Along with the existence of the splinter groups in any society, the disintegration myth arises inevitably. This is not due to the historic necessity referred to the movement, but because it is believed that social cohesiveness will always be broken by the religious subversion. Therefore, the way to handle any subversion is normally power approach, starting from decree of deviation, stigmatization which causes social unrest in the society, and even religion disgracing. The effect is violence to the splinter groups movement in the name of religion. For this time being, dialogue (although does not touch the essential part of the problem) is always focused on the status of the religions. While the relationship among religions is protected under the constitution and nationalism imagination, the dialogue intra religion is avoided which makes any splinter groups movement result in mass violence either cognitively, verbally, or physically.